Amphibians and reptiles of Texas : with keys, taxonomic synopses, bibliography, and distribution maps - Dixon, James Ray (W.L. Moody Jr. natural history series, 2000)
"In this revised edition of Amphibians and Reptiles of Texas, James R. Dixon adds to and updates the extensive information given in the first edition. A new section on conservation issues highlights some of the problems facing the continued survival of amphibians and reptiles, particularly commercial collecting and habitat destruction. Taxonomic changes have been made to reflect the latest scientific information, and the extensive listing of the literature on Texas amphibians and reptiles has been updated through April, 1999. Going back to the writings of French botanist Jean Louis Berlandier, who encountered Texas herpetofauna during his travels from 1828 to 1834, this list covers more than 150 years of inquiry into the state's species." "Professional and amateur herpetologists as well as environmentalists, wildlife specialists, campers, and hikers will find the dichotomous keys useful for identifying species at hand."--Jacket